Increasing Learning Motivation by Developing Interactive Multimedia In Physical, Sport And Health Education (PJOK) Lessons at SMP Negeri 14 Madiun - Ilham Putra Nugraha; Gigih Siantoro; Nanik Indahwati; Taufiq Hidayat (STKIP Muhammadiyah Kuningan, 2023)
This study aims to test the application of interactive multimedia based on an articulate storyline to increase student motivation in PJOK lessons. Work Safety material focuses on research studied by grade VIII students at SMP Negeri 14 Madiun. This research is classified as development research developed using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The data analysis techniques used are quantitative and qualitative descriptive analysis techniques. The results of research on interactive multimedia development based on articulate storyline work safety material developed according to material experts, media experts, and linguists are very valid, with a percentage of 84%, 84%, and 88%. Student learning motivation using articulate storyline learning media is classified as a very high category with an average percentage of 86%. The results of this study show that the development of interactive multimedia based on an articulate storyline can increase student motivation in class VIII PJOK lessons at SMP Negeri 14 Madiun